Comparative evaluation of a simple and sensitive assay for detection of orthomyxo and paramyxoviruses - J. N. S. S. Couceiro; E. S. S. Couceiro; A. M. V. Pinto; R. D. Machado; M. C. Cabral (Memorias do Instituto Oswaldo Cruz, 1994)
Studies were done to evaluate comparatively the traditional HA assay and a more recently introduced lectin-neuraminidase (LN) methodologyin search of a simple and sensitive assay for virus detection during laboratorial diagnosis. The results proved the value of LN assay as a sensitive methodologyfor detection of virus particles, presenting results at least equal to those obtained by HA (hemagglutination) assay, with significant values of accumulated frequencies for LN/HA factors (ratios between LN and HA titers) higher than two. The accumulated values of frequencies for LN/HA factors as high as four were very significant, 72.7 (per cent) for influenzavirus and 60.7 (per cent) for Newcastle disease virus (NDV), moreover accumulated frequencies for LN/HA factors even as high as 32 were due to influenzavirus (45.4 per cent) and NDV (7.2 per cent) samples. After the storage period, most of those concentraded samples that even did not present HA titers could be detected through LN assay, demonstrating a lower threshold for virus detection.